Experimental analysis of a multi-phase resonance-based fault current limiter prototype under symmetrical and asymmetrical faults - Kucukaydin, Baris; Arikan, Oktay; Isen, Evren (ELSEVIER SCIENCE SA, 2024)
Expansion of power systems and involving more distributed generation cause to increase in fault current levels. This paper presents a three-phase resonance-based solid -state fault current limiter (FCL) prototype that has series and parallel resonance modes developed to suppress fault currents of power systems. The laboratory-scaled prototype is located on a three-phase test circuit and has been examined with the fault types of three-phase, three phase-to-ground, two phase-to-ground, and phase-to-ground. The performance and effectiveness of the proposed series-parallel resonance-type fault current limiter (SPRFCL) are validated with the comparison of Matlab/Simulink simulations and experimental test results. Fault currents in different types of faults are limited to an allowable value at high rates and experimental results are considerably close to current values obtained from each fault simulation. Fault currents of faulted phases are restricted with the limiting rates ranging from 75 % to 85 % concerning prospective fault currents in the non-FCL situations. Short -circuit test results of the prototype of SPRFCL that is supplied from a 380 V grid revealed that it acts stable and successful operation regardless of fault type. Accordingly, it has a favorable circuit design for power system applications.
Keywords: Experimental test; Fault current limiter; Parallel resonance; Series resonance; Three-phase prototype; TRANSIENT STABILITY; ENHANCEMENT; PERFORMANCE; CAPABILITY; NETWORK; BREAKER; RIDE; Engineering